Mental Health Promotion as a Prevention and Healing Tool for Issues of Youth Suicide in Canadian Aboriginal Communities - Wortzman, Rachel L. (First Peoples Child & Family Review, 2009)
This article discusses the appropriateness of using mental health promotion as a prevention and healing tool for Canadian Aboriginal youth dealing with issues of suicide. Strengths of mental health promotion in the context of this population include its emphasis on community-wide approaches, consideration of root causes of mental health issues, recognition of culture as a protective factor, and integration of diverse forms of knowledge. Limitations include an inadequate role for spirituality, lack of culturally-sensitive program evaluation, and emphasis on Western patterns of time, space, and communication. In response to this analysis, recommendations are proposed that could guide the development of future mental health promotion programs.